Understanding Jainism - Babb, Lawrence A. (Edinburgh : Dunedin Academic Press, 2015)
The author introduces one of the world's oldest religions, Jainism, which prescribes nonviolence towards all living beings, and emphasizes spiritual independence.
Title Page verso; Title page; toc; Contents; List of Illustrations; Romanisation and Pronunciation; Acknowledgements; Introduction; Charter; In History; Liberation's Roadmap; Strivers; Supporters; A Moral Cosmos; Social Context; current; Afterword; References; Glossary; Further Reading; Index.
Print version record.
Keywords: Jainism -- India; Jainism -- History; Jainism; Religion; Jainism; India; RELIGION / Comparative Religion; Electronic books